Bezdroza dziejow Polski : kraj i emigracja po 1 wrzesnia 1939 r. - Wyrwa, Tadeusz (Lublin : Norbertinum, 1998)
A history of Poland after September 1939, in the events in peoples lives, both those who remained in Poland and of those who emmigrated.
Keywords: Poland -- History -- 20th century